Regulated expression of human beta-defensin-2 leads to altered phenotype and growth patterns of cultured human embryonal kidney cells - Zhuravel, E.; Lytvyn, D.; Soldatkina, M.; Zeleniy, S.; Shestakova, T.; Pogrebnoy, P. (Інститут експериментальної патології, онкології і радіобіології ім. Р.Є. Кавецького НАН України, 2006)
Aim: To create cell line with regulated expression of human beta-defensin-2 (hBD-2) and evaluate the influence of expressed peptide on its phenotypic and growth patterns. Materials and Methods: Using cloning techniques, on the base of human embryonic kidney cells of HEK293T line, stable T-rex HEK-hBD2-m cell subline expressing mature biologically active hBD-2 molecule upon the presence of tetracycline in culture medium was generated. The morphological patterns, growth characteristics and colony forming activity of these cells were studied using routine techniques. Results: T-rex HEK-HBD2-m cell subline was shown to express both mRNA and hBD-2m protein upon the presence of 1 µg/ml tetracycline in culture medium as it was demonstrated by RT-PCR and immunocytochemical approach. Upon prolonged expression of hBD-2, the cells acquired special features: they lost ability to grow in monolayer in vitro and to form colonies in soft agar, characteristic to parental HEK293T cells, but possess higher growth rate and longer survival in FBS-free medium than wild type cells. Conclusion: Expression of hBD-2 in T-rex HEK-HBD2-m cell subline results in specific biological consequences that favor cell survival. Цель: создать линию клеток с регулируемой экспрессией бета-дефенсина-2 человека (hBD-2) и проанализировать влияние экспрессии этого пептида на особенности фенотипа и рост клеток. Материалы и методы: клеточная сублиния T-rex HEK hBD2-m, экспрессирующая биологически активную зрелую форму hBD-2 при индукции клеток тетрациклином, получена путем клонирования на основе эмбриональных клеток почки человека линии HEK293T. Морфологические особенности, характеристики роста и показатели колониеобразования в полужидкой среде исследовали стандартными методами. Результаты: с помощью методов РТ-ПЦР и иммуноцитохимии показано, что сублиния клеток T-rex HEK-HBD2- экспрессирует hBD2 в присутствии 1 µг/мл тетрациклина в среде инкубации. Продолжительная экспрессия hBD-2 приводила к тому, что клетки утрачивали способность образовывать монослой при культивировании in vitro и образовывать колонии в полужидкой среде, но характеризовались более высокой скоростью роста и способностью к более продолжительному выживанию в бессывороточной среде, чем исходная линия клеток HEK293T. Выводы: экспрессия hBD-2 в сублинии клеток T-rex HEK-HBD2- cell обусловливает специфические биологические эфеекты, способствующие выживанию клеток.